MEDIASI SEBAGAI ALTERNATIVE DISPITE RESULOTION TERHADAP PERKARA PERCERAIAN - A Hashfi Luthfi; Firqah Annajiyah Mansyuroh (Fakultas Syariah dan Ekonomi Islam, 2022)
The judicial system in Indonesia has recognized mediation as an alternative dispute resolution. The Supreme Court of the Republic of Indonesia through Supreme Court Regulation (Perma) Number 01 of 2016 concerning Mediation Procedures in Courts has integrated mediation into the proceedings in court. as an instrument to overcome the accumulation of cases. This mediation is applied as part of the event in civil cases in the religious courts and general courts. All civil disputes submitted to the court of first intance must first be resolved throught reconciliation with the help of a mediator, namely a neutral party who assists the parties in the negotiation process in order to seek various possible dispute resolitions without resorting to a way of deciding or completing a case settlement. This study uses a normative juridical approach by using data collection techniques through library research methods. The results of this study is factors that influence the success of mediation include the disputing parties, the problem that causes the dispute and the quality of the third party or mediator.